Structure and mechanism of the complex between cytochrome P4503A4 and ritonavir - Sevrioukova, Irina F. (National Academy of Sciences, 2010)
Ritonavir is a HIV protease inhibitor routinely prescribed to HIV patients that also potently inactivates cytochrome P4503A4 (CYP3A4), the major human drug-metabolizing enzyme. By inhibiting CYP3A4, ritonavir increases plasma concentrations of other anti-HIV drugs oxidized by CYP3A4 thereby improving clinical efficacy. Despite the importance and wide use of ritonavir in anti-HIV therapy, the precise mechanism of CYP3A4 inhibition remains unclear. The available data are inconsistent and suggest that ritonavir acts as a mechanism-based, competitive or mixed competitive-noncompetitive CYP3A4 inactivator. To resolve this controversy and gain functional and structural insights into the mechanism of CYP3A4 inhibition, we investigated the ritonavir binding reaction by kinetic and equilibrium analysis, elucidated how the drug affects redox properties of the hemoprotein, and determined the 2.0 Å X-ray structure of the CYP3A4-ritonavir complex. Our results show that ritonavir is a type II ligand that perfectly fits into the CYP3A4 active site cavity and irreversibly binds to the heme iron via the thiazole nitrogen, which decreases the redox potential of the protein and precludes its reduction with the redox partner, cytochrome P450 reductase.